Micro finite element analysis of dental implants under different loading conditions - Marcián, Petr; Wolff, Jan; Horáčková, Ladislava; Kaiser, Jozef; Zikmund, Tomáš; Borák, Libor (Computers in biology and medicine, 2018)
Osseointegration is paramount for the longevity of dental implants and is significantly influenced by biomechanical stimuli. The aim of the present study was to assess the micro-strain and displacement induced by loaded dental implants at different stages of osseointegration using finite element analysis (FEA). Computational models of two mandible segments with different trabecular densities were constructed using microCT data. Three different implant loading directions and two osseointegration stages were considered in the stress-strain analysis of the bone-implant assembly. The bony segments were analyzed using two approaches. The first approach was based on Mechanostat strain intervals and the second approach was based on tensile/compression yield strains. The results of this study revealed that bone surrounding dental implants is critically strained in cases when only a partial osseointegration is present and when an implant is loaded by buccolingual forces. In such cases, implants also encounter high stresses. Displacements of partially-osseointegrated implant are significantly larger than those of fully-osseointegrated implants. It can be concluded that the partial osseointegration is a potential risk in terms of implant longevity.
Keywords: Finite Element Analysis; Mandible; Signal Processing, Computer-Assisted; Humans; zubní implantáty; Models, Biological; počítačové zpracování signálu; Osseointegration; lidé; Stress, Mechanical; analýza zatížení zubů; rentgenová mikrotomografie; Dental Implants; Male; osteointegrace; biologické modely; X-Ray Microtomography; Dental Stress Analysis; mandibula; biomechanika; mužské pohlaví; Biomechanical Phenomena; analýza metodou konečných prvků; mechanický stres